Perlindungan Hukum Terhadap Guru Honorer dalam Pemenuhan Hak Jaminan Sosial Ketenagakerjaan di Kabupaten Bekasi - Wulandari, Rahmah; Piolika, Perga; Bukutubun, Laurensia Inda; Akbarian, Kiham; Efendi, M Irfan (Journal of Industrial Relations Studies, 2026)
This study aims to analyze the legal protection for honorary teachers in fulfilling their social security employment rights in Bekasi Regency and to examine the local government’s responsibilities. A normative juridical method with statutory, conceptual, and case study approaches was used. The results show that many honorary teachers are not registered as BPJS Ketenagakerjaan participants due to the absence of local regulations, limited funding, and low legal awareness. Institutions failing to comply may face administrative sanctions, fines, or criminal penalties. The local government should establish regional regulations, allocate contribution subsidies, and strengthen coordination with BPJS Ketenagakerjaan to ensure fair and sustainable social protection. This study emphasizes that social security for honorary teachers is not only a legal obligation but also a moral responsibility of the state